Au cœur de la matière : apports et limites de la science des matériaux à la question des « fausses » porcelaines chinoises - Ariane Pinto (Les Cahiers de Framespa)
The imitation of Chinese porcelains is an important issue in archaeology and art history. Decorations or style can be easily copied, but the constitutive materials of the object are the result of a specific technical process, much more difficult to imitate when raw materials are no longer accessible or when the manufacturing process has evolved. The use of a “material science” approach, focused on the composition of porcelains, may allow one to identify some characteristics which can serve as expertise markers. This article presents the inputs and limits of such an approach, through some examples on Chinese blue and white porcelains.